2w+3=4w+2

Simple and best practice solution for 2w+3=4w+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2w+3=4w+2 equation:


Simplifying
2w + 3 = 4w + 2

Reorder the terms:
3 + 2w = 4w + 2

Reorder the terms:
3 + 2w = 2 + 4w

Solving
3 + 2w = 2 + 4w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-4w' to each side of the equation.
3 + 2w + -4w = 2 + 4w + -4w

Combine like terms: 2w + -4w = -2w
3 + -2w = 2 + 4w + -4w

Combine like terms: 4w + -4w = 0
3 + -2w = 2 + 0
3 + -2w = 2

Add '-3' to each side of the equation.
3 + -3 + -2w = 2 + -3

Combine like terms: 3 + -3 = 0
0 + -2w = 2 + -3
-2w = 2 + -3

Combine like terms: 2 + -3 = -1
-2w = -1

Divide each side by '-2'.
w = 0.5

Simplifying
w = 0.5

See similar equations:

| 1/2(x-4)=2(x+2) | | -9v-4=-v-12 | | 2x^2-19+9=0 | | 4t-18=-t-13 | | 4t-18=-3-13 | | 4b+5=19 | | 9v+19=7v+5 | | 5m+m=132 | | 4z-3=-3z-3 | | x-8.6=3.2 | | 10-7lnx=-4 | | r-7/9=20/9 | | u/3-10=-14 | | 3x(x+7)=36 | | 9+24=3x | | 2x^3+x^2+7=-3 | | (2x^2y^3)^2(-4x^4)^3/(xy)4x^6y^3)^4 | | 15/55 | | 3x+4y+5x-3y= | | g(x)=4x^2-48x+7 | | 23+x=11 | | 1/8(x-16)=x+5 | | 3x-7(7x+9)=3-x | | -2x^2-9-3x-2x^2+8x+7= | | 25x^2=53 | | ax^2+(a+1)x-1=0 | | log(15x+40)-log(2x+5)=1 | | 25x^2-36=17 | | (3x+10)(2x)=90 | | x-7.3=3.2 | | 8y-2x=10+4x-6y | | (3x+10)+(2x)=90 |

Equations solver categories